الإفصاح المحاسبي في القوائم المالية للشركات الجزائرية دراسة حالة الشركات المدرجة في البورصة خلال الفترة (2015-2017) - بلعجوز, الحسين (جامعة مسيلة, 2018)
This study is intended to highlight the issue of accounting disclosure in the financial statements of companies in accordance with International Accounting Standards (IAS). The accounting disclosure in the financial statements of companies is a tool for communicating financial information that reflects the performance of the company and its financial position to serve external and related parties. Although there is no general agreement on the nature of the elements required by each category of users of the financial statements, a minimum amount of information for each category should be provided. This policy included in the International Accounting Standard IAS (1) "Presentation of Financial Statements", which provides the minimum requirements that must be disclosed in the financial statements of the companies. The main objective of this study was to test the extent to which the listed Algerian shareholding companies comply with accounting requirements in accordance with International Accounting Standard IAS 1 during the period 2015-2017. In order to achieve the objectives of this study and given the nature of the data related to them, the researchers applied the method of Dummy Variables. A set of items has been selected for accounting disclosure requirements based on previous studies and international accounting standards as well as the accounting system, which amounted to 70 items relating to accounting disclosure in the financial statements. The extracted data were converted from qualitative variables to Dummy Variables, so that if the company complies with accounting disclosure requirements, the nominal variable (1) is given. If not, the nominal variable (0) is given for the whole period ranging from 2015 to 2017 for the companies under study. It means that it is a series of values that takes frequencies (0-1) over 3 years. The researchers calculated the percentages and applied the Binomial Test, which is consistent with the nature of the data, to determine the total proportion of the companies' compliance with the accounting disclosure requirements in the studied sample during the period 2015-2017. The study found that the percentage of the Algerian shareholding companies' commitment to the accounting disclosure requirements during the reviewed period varied from one company to another, showing that the highest commitment percentage (70%) was registered with Eurasia, followed by Biofarm (67%), Ruwiba and Sedal (59%). The lowest commitment was recorded by Aliance Insurance Company (42%). The researchers found that the ratios of the companies' compliance with each list vary from one company to another, especially for the two lists (treasury flows, changes in equity) as well as other aspects of disclosure that have to be presented in the annexes to the accounting disclosure requirements, which were not sufficiently disclosed by the Algerian listed shareholding companies. This last reached 40%, while the total percentage of the Algerian listed shareholding companies in accordance with IAS 1 is estimated at (59%), which in the opinion of the researchers is considered significant, but it represents only the minimum mandatory disclosure to which listed shareholding companies are committed through Algerian accounting and taxation laws.
Keywords: Accounting Disclosure, International Accounting Standards, shareholding companies, Stock Exchange. Jel Classification Codes: M41.